Antimicrobial Prescribing Practices in Small Animal Emergency and Critical Care - Robbins, Sarah N.; Goggs, Robert; Lhermie, Guillaume; Lalonde-Paul, Denise F.; Menard, Julie (Frontiers in Veterinary Science, 2020)
Background: Antimicrobial use contributes to emergence of antimicrobial resistance. It was hypothesized that antimicrobial prescribing behavior varies between the emergency (ER) and critical care (CC) services in a veterinary teaching hospital. This study aimed to: (i) describe antimicrobial prescribing patterns in the ER and CC services; (ii) assess adherence to stewardship principles; (iii) evaluate the prevalence of multidrug resistant (MDR) bacterial isolates. Methods: Institution electronic medical records were queried for all antimicrobial prescriptions from the ER and CC services between 1/1/2017 and 12/31/2017. Prescriptions were manually reviewed, and the following data recorded: drug, dosage, duration, diagnosis, outcome, hospitalization duration, culture submission, and susceptibility results. Results: There were 5,091 ER visits, of which 3,125 were not transferred to another service. Of these emergency visits, 516 (16.5%) resulted in 613 antimicrobial drug prescriptions. The most commonly prescribed drugs for the ER were amoxicillin/clavulanate (n = 243, 39.6%), metronidazole (n = 146, 23.8%), and ampicillin/sulbactam (n = 55, 9.0%). The most common reasons for antimicrobial prescriptions were skin disease (n = 227, 37.0%), gastrointestinal disease (n = 173, 28.2%), and respiratory disease (n = 50, 8.2%). For ER patients 18 cultures were submitted, equivalent to a 3.5% submission rate. The CC service managed 311 case visits for 822 patient days. Of these, 133 case visits (42.7%) resulted in 340 prescriptions. The most commonly prescribed drugs for the CC service were ampicillin/sulbactam (n = 103, 30.3%), enrofloxacin (n = 75, 22.1%), and metronidazole (n = 59, 17.4%). The most common reasons for antimicrobial prescriptions were gastrointestinal disease (n = 106, 31.2%), respiratory disease (n = 71, 20.9%), and sepsis (n = 61, 17.9%). On the CC service, 46 patients had ≥1 culture submitted, equivalent to a 34.6% submission rate. Of patients prescribed antimicrobials, 13/38 (34%) with urinary tract disease, 2/28 (7%) with pneumonia, 1/11 (9%) with canine infectious respiratory disease complex and 2/8 (25%) with feline upper respiratory infection were compliant with published guidelines. Conclusions: Antimicrobial prescription was common in both ER and CC services and followed similar patterns. Adherence to published guidelines for urinary and respiratory infections was poor.